Therapeutic Targeting of Pancreatic Cancer via EphA2 Dimeric Agonistic Agents - Ahmed F. Salem; Luca Gambini; Parima Udompholkul; Carlo Baggio; Maurizio Pellecchia (MDPI AG, 2020)
Recently, we reported on potent EphA2 targeting compounds and demonstrated that dimeric versions of such agents can exhibit remarkably increased agonistic activity in cellular assays compared to the monomers. Here we further characterize the activity of dimeric compounds at the structural, biochemical, and cellular level. In particular, we propose a structural model for the mechanism of receptor activation by dimeric agents and characterize the effect of most potent compounds in inducing EphA2 activation and degradation in a pancreatic cancer cell line. These cellular studies indicate that the pro-migratory effects induced by the receptor can be reversed in EphA2 knockout cells, by treatment with either a dimeric natural ligand (ephrinA1-Fc), or by our synthetic agonistic dimers. Based on these data we conclude that the proposed agents hold great potential as possible therapeutics in combination with standard of care, where these could help suppressing a major driver for cell migration and tumor metastases. Finally, we also found that, similar to ephrinA1-Fc, dimeric agents cause a sustained internalization of the EphA2 receptor, hence, with proper derivatizations, these could also be used to deliver chemotherapy selectively to pancreatic tumors.